2018
DOI: 10.1007/s00221-018-5298-z
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin-containing neurons in the olfactory bulb send collateralized projections into medial amygdaloid and arcuate hypothalamic nuclei: neuroanatomical study

Abstract: Ghrelin, a gastrointestinal hormone, is a modulator of the sense of smell. The main source of ghrelin in the central nervous system has been mainly observed in specific populations of hypothalamic neurons. An increasing number of studies have reported ghrelin synthesis and its effect on neurons outside the hypothalamus. Ghrelin and its receptors are expressed in the olfactory bulbs and in other centres of the brain, such as the amygdala, for processing olfactory signals, pyramidal neurons of the cerebral corte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 46 publications
0
16
1
Order By: Relevance
“…It has recently been shown that hormones whose homeostatic signaling may be impaired in obesity (Baly et al, 2007;Aime et al, 2012;Russo et al, 2018), modulate olfactory performance in humans. More specifically, intranasally applied insulin as well as intravenously applied ghrelin improve olfactory function (Tong et al, 2011;Thanarajah et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that hormones whose homeostatic signaling may be impaired in obesity (Baly et al, 2007;Aime et al, 2012;Russo et al, 2018), modulate olfactory performance in humans. More specifically, intranasally applied insulin as well as intravenously applied ghrelin improve olfactory function (Tong et al, 2011;Thanarajah et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our results can lead to at least two different interpretations. On the one hand, ICV Ex-4 administration could activate ghrelin-producing neurons adjacent to the 3rd ventricle to induce feeding, and then Ex-4 may permeate the blood-brain barrier to further stimulate ghrelin-producing cells in the stomach to subsequently regulate feeding [30, 31]. On the other hand, central Ex-4 administration may regulate gastric ghrelin expression directly through the neural signals transmitted by the vagal nerve, which in turn regulates feeding [32-34].…”
Section: Discussionmentioning
confidence: 99%
“…The ghrelin receptor GHS-R1a is expressed in hypothalamic neuropeptide Y-(NPY) and agouti-related peptide-(AgRP) expressing neurons (NPY/AgRP neurons), somatotropic cells and luteinising hormone (LH)-, thyroid-stimulating hormone (TSH)-, adrenocorticotropic hormone (ACTH)-and prolactin-(PRL) releasing cells in the anterior pituitary [26][27][28][29]. A lower expression of GHS-R1a is found in other brain regions such as the cingulate gyrus [30][31][32], amygdala, olfactory bulb and in hypothalamic ghrelin-receptive neurons adjoining the dorsal vagal complex (DVC) [33]. The expression of GHS-R1a is found across three distinct brain areas: pituitary gland (i.a.…”
Section: Ghrelin and The Central Nervous Systemmentioning
confidence: 99%